Verfassungsblog: on matters constitutional - Steinbeis, Maximilian (Max Steinbeis Verfassungsblog gGmbH, 2009)
Verfassungsblog is a journalistic and academic forum of debate on topical events and developments in constitutional law and politics in Germany, the emerging European constitutional space and beyond. It sees itself as an interface between the academic expert discourse on the one hand and the political public sphere on the other.
Gesehen am 06.12.2023
Keywords: Weblog